Refelxão sobre o papel do supervisor pedagógico no contexto da educação escolar. Estudo de caso de uma supervisora pedagógica - Jorge, José Reis (2018)
The aim of this study is to produce a reflection on the role of the pedagogical supervisor as well as on the educational processes, highlighting relevant aspects such as the acquisition by the supervisor of a reflexive attitude and of a capacity for active listening. The problem is presented with an analysis of the growing importance of the supervisor’s role. The qualitative method was chosen, considering that this was a case study, with a single participant. A narrative approach was developed within the line of research on “professional life”. The study concludes that the role of the reflexive supervisor is fundamental in order to achieve the best results in an educational setting